Predictors of Outcome in Intracerebral Hemorrhage and Performance of Hemphill ICH Score and GVS Score (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: The outcome of intracerebral hemorrhage (ICH) is gloomy. There are several scoring systems for predicting its outcome.Objective: The purpose of the present study was to observe the predictors of outcome in ICH patients and to assess the performance of ‘Hemphill ICH score’ and ‘GVS score’.Methodology: This cohort study involved patients of ICH admitted within 72 hours of acute event in July to December 2017 in the Department of Neurology at National Institute of Neurosciences (NINS) & Hospital, Dhaka, Bangladesh. Clinical and radiological data at admission and in-hospital events were obtained from medical records. Patients who were discharged from the hospital were interviewed at 30th day after event by face to face interview or over telephone. Follow up data was not found for 4 patients.Results: This study involved 115 patients of ICH [median age 60 years (interquartile range, IQR 50-70); 46% (53/115) female]. In-hospital and 30-day mortality of the ICH patients was 22% (25/115: 95% CI 15-30%) and 38% (42/111; 95% CI 29–48%) respectively. There was almost perfect agreement between Hemphill ICH score and GVS score (p